Associated Factors to Seroprevalence of Ehrlichia spp. in Dogs of Quintana Roo, Mexico - Pedro Pablo Martínez-Vega; Manuel Emilio Bolio-Gonzalez; Roger Iván Rodríguez-Vivas; Eduardo Gutierrez-Blanco; Carlos Pérez-Osorio; Sandra Luz Villegas-Perez; Carlos Humberto Sauri-Arceo (Journal of Tropical Medicine)
The objective of this study was to determine the seroprevalence to Ehrlichia spp. in dogs from Xcalak, Quintana Roo, Mexico, and the associated factors. Serum samples were obtained from 118 dogs and used in an indirect immunofluorescent assay test for the detection of antibodies against Ehrlichia spp. A questionnaire was used to obtain information about possible variables associated with seroprevalence. These variables were analyzed through Chi2 test and logistic regression. Dog seroprevalence of antibodies against Ehrlichia spp. was 64% (75/118). Fifty-two percent (61/118) of dogs had tick infestation which was identified as Rhipicephalus sanguineus sensu lato. Anemia was observed in 36% of dogs. Leucopenia (2.5%), thrombocytopenia (70%), and hemorrhage (14%) were also observed. Thirty-one percent (23/75) of dogs with anemia, 4% (3/75) of dogs with leucopenia, 80% (60/75) of dogs with thrombocytopenia, 17% (13/75) of dogs with hemorrhages, and 59% (44/75) of dogs with ticks were positive for Ehrlichia spp. antibodies. The factors associated with seroprevalence were age (1–3 and >3 years old, OR = 7.77 and OR = 15.39, resp.), tick infestation (OR = 3.13), and thrombocytopenia (OR = 3.36). In conclusion, seroprevalence of Ehrlichia spp. was high in the community of Xcalak and its associated factors were age, tick infestation, and thrombocytopenia.